Emotional Intelligence in Relation to Occupational Self-efficacy and Personality of Secondary School Teachers - Sahni, Dr Madhu (INDIAN EDUCATIONAL REVIEW, 2012)
This study endeavoured (i) to assess the level of emotional intelligence of secondary school teachers, and (ii) to study the influence of occupational self-efficacy, personality and their interaction on emotional intelligence of secondary school teachers. A sample of 240 secondary school female teachers was randomly selected from various secondary schools of state Haryana. Data analysis revealed (i) significant independent effect of occupational self-efficacy and personality on emotional intelligence; and (ii) significant two factor interactive effect of variables on interpersonal management skill of secondary school teachers.